Virtual play and real connections: unpacking the impact of rice farming simulation video games - Nishimura, Takeshi; Taguchi, Junko; Kumazawa, Terukazu; Hayashi, Kengo (Frontiers in Computer Science, 2024)
This study investigates how the rice farming simulation video game Sakuna: Of Rice and Ruin affects interest in real-world agriculture and the inclination to start farming amidst Japan's declining farming population. We surveyed 428 Japanese residents, including not only game players but also those who watch the game live or are merely aware of its existence. We also interviewed an individual who started rice farming after playing the game. The findings indicate that the game successfully stimulates greater interest in agriculture and somewhat motivates players to consider farming, more than just viewers or those who are aware of it. Moreover, individuals with real-life connections to agriculture, such as farming experience or professional connections, were optimistic about the transition from game to reality. The study suggests that rice farming simulation games can foster expectations of developing an interest in agriculture and potentially embarking on farming careers, demonstrating the game's significant impact beyond entertainment. agriculture, but the National Federation of Agricultural Cooperative Associations (Zen-Noh) in Japan promoted Sakuna via social media, including distributing a PDF booklet on actual rice farming 2 .This indicates that an agricultural organization is making a coordinated effort to cultivate interest in farming among young people. This initiative is driven by a decrease in the farming population and a looming crisis in the sustainability of the agricultural sector.Japan is known for having one of the world's most rapidly aging societies (Cutler et al., 1990;Anderson and Hussey, 2000), which poses significant challenges across various sectors, especially agriculture (Jöhr, 2012). The agricultural sector vividly reflects this demographic shift, with a marked reduction in the farming population over the last six decades (Figure 1). As of 2020, a staggering 79.9% of this population was 65 years or older, with only a small fraction, 4.9%, being under 40. On the other hand, while the influx of new farmers in Japan includes older individuals transitioning postretirement, a noteworthy proportion also includes younger people (Figure 2). Therefore, increasing the younger generation's interest in agriculture is essential to strengthen this trend.